Ecological Shifts and Cultural Continuity: The Case of Zhuang Liao Songs in Guangxi, China (Música Hodie, 2025)
The Zhuang Liao Songs (壮族嘹歌) is a traditional duet folk song that is popular in Pingguo County, Guangxi, and carries the historical memory and cultural identity of the Zhuang community. With the rapid development of modernization, urbanization, and digital media, the musical ecological environment in which Zhuang Liao Songs exists has changed significantly. Based on the theory of music ecology and combined with a 12-month ethnographic field survey, this paper explores how Zhuang Liao Songs can achieve adaptation and cultural continuity in the new ecological environment. The study found that Zhuang Liao Songs has expanded its ecological niche through campus education, public performances, and digital communication, and the community has also actively negotiated cultural identity between tradition and innovation. The article proposes a “multi-level ecological adaptation model”, emphasizing that traditional music should be regarded as a dynamic ecosystem, providing theoretical support for understanding the relationship between cultural change and continuity, and providing empirical references for the protection practice of intangible cultural heritage.